The role of Abdullah Qadiri in Uzbek novels (Zien Journal of Social Sciences and Humanities, 2021)
This article deals with the life and work of Abdullah Qadiri, his thoughts on the Jadid movement, and the novels he wrote as the founder of Uzbek romance